2014
DOI: 10.1123/rsj.2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Participation in Campus Recreation Based on Activity Type

Abstract: In this study, we examined differences in leisure motivation on the basis of the type of campus recreational activity in which a student was engaged. Specifically, campus recreational activities included aquatics, group fitness, intramural sports, informal sports, and informal fitness. The Leisure Motivation Scale (Beard and Ragheb, 1983) was completed by subjects after they engaged in a campus recreation activity. A 95% confidence level was established a priori, but a Bonferroni adjustment resulted in α ≤ .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The LMS was developed by Beard and Ragheb (1983) and organizes participant motivation into the following four categories: intellectual, social, competency/mastery, and stimulus avoidance. Beggs et al (2014) found that competency/mastery factors were the strongest motivators for participants in all activity areas. Their findings support literature from Kanters and Forrester (1997), and Beggs and Elkins (2010) that demonstrates campus recreation participation may be driven by a desire for competition and achievement.…”
Section: Review Of Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…The LMS was developed by Beard and Ragheb (1983) and organizes participant motivation into the following four categories: intellectual, social, competency/mastery, and stimulus avoidance. Beggs et al (2014) found that competency/mastery factors were the strongest motivators for participants in all activity areas. Their findings support literature from Kanters and Forrester (1997), and Beggs and Elkins (2010) that demonstrates campus recreation participation may be driven by a desire for competition and achievement.…”
Section: Review Of Literaturementioning
confidence: 93%
“…Research has indicated that socialization is an important motivator for college students participating in campus recreation activities (Artinger et al, 2006;Beggs and Elkins, 2010). Beggs, Nicholson, Elkins, and Dunleavy (2014) found that beyond personal mastery, socialization was the next highest motivator for a group of 300 campus recreation students that they surveyed. These findings supported the notion that campus recreation centers have value beyond a place to exercise on college campuses.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Avoiding stimulus evaluates motivation to participate in leisure activities to avoid daily activities. Avoiding social contact is related to recreational activities to relax and rest [11]. In the relevant literature there are various studies investigating motivation to participate in recreational activity.…”
Section: Experience Motivationmentioning
confidence: 99%
“…These studies have stressed the importance of moving away from simple investigations of exercise-based activities for noncollegiate athletes and athletic motivations of varsity sport participants, and toward more inclusive research of sport at all levels (Kilpatrick, Herbert, & Bartholomew, 2005). Within the campus recreational sport environment in particular, motivation has been investigated in reference to the holistic health benefits of such participation (Artinger et al, 2006), utilizing a variety of theoretical frameworks (Cooper, Schuett, & Phillips, 2012), and investigating differences in motivation for different activity types (Beggs, Nicholson, Elkins, & Dunleavy, 2014). All of these studies have built upon the previous knowledge of sport participant motivation within the campus environment, and this study seeks to build upon that foundation through the specific measurement of motivations of swimming participants in this environment.…”
Section: Review Of Literaturementioning
confidence: 99%